Highly active antiretroviral therapy adherence among HIV-POSITIVE women in Southern Ethiopia - Demissie, Alemayehu Abebe; Rensburg, Elsie Janse van (Frontiers in Pharmacology, 2024)
Adherence to Highly Active Antiretroviral Therapy (HAART) medication is the major predictor of HIV/AIDS treatment success. Poor adherence to HAART creates the risk of transmitting HIV, deteriorating health conditions, treatment failure, increased occurrences of drug-resistant HIV, morbidity and mortality. The objective of the study was to explore and describe factors influencing HAART adherence among HIV-positive women in Southern Ethiopia. Methods: A hospital-based descriptive cross-sectional survey was used among 220 randomly selected respondents. Data was collected with a structured interview guide after each respondent had given consent to take part in the study. The collected data was entered into and analyzed by using the Statistical Package for Social Sciences (SPSS) software program version 27.The level of self-reported adherence (measured by dose) to HAART in the past thirty days was found to be 82.7%. In multivariate analysis, the divorced/separated HIVpositive women had poor adherence to their HAART medication as compared to those who were married [AOR: 2.94, 95% CI: (1.02-8.44)]. Respondents who used reminders in their medication were 75% less likely to be poorly adherent to their HAART medication than those who did not use reminders [AOR: 0.25, 95% CI: (0.06-0.97)]. Those who self-reported depression, perceived stigma, and low perceived susceptibility had poor adherence to their HAART than those who did not report depression, perceived stigma, and low perceived susceptibility [AOR:2.34, 95% CI: (1.01-5.42)], [AOR:2.37, 95% CI: (1.06-5.34)], and [AOR: 4.1, 95% CI: (1.53-11.1)] respectively. HIV-positive women who self-reported low perceived severity were poorly adherent to HAART than those who self-reported high perceived severity [AOR: 2.92, 95% CI: (1.14-7.47)].Factors including being divorced/separated, not using reminders, depression, perceived stigma, perceived susceptibility, and perceived severity negatively impact HIVpositive women's adherence to HAART.